Identification and some biochemical properties of the major XBL gene product of bovine leukemia virus. - Sagata, N (1985)
Using a rabbit antiserum directed against a synthetic oligopeptide whose sequence was deduced from the nucleotide sequence of the XBL gene of bovine leukemia virus, we detected a 38-kDa protein in virus-producing cell lines. In vitro translation of hybrid-selected RNA unequivocally demonstrates that this protein, designated p38(XBL), is indeed encoded by the XBL gene. Unlike the other virus-encoded proteins, however, p38(XBL) resides within the cells without being incorporated into virions. It undergoes no gross post-translational modifications and has a relatively short half-life (5-6 hr) in vivo. Furthermore, cell fractionation combined with pulse-chase experiment reveals that a significant fraction (more than half) of the p38(XBL) localizes to the nucleus of the infected cell after synthesis. We conclude that the XBL gene of bovine leukemia virus is a functional gene encoding a nonvirion protein p38(XBL), which possibly functions within the nucleus of the infected cell to regulate viral or cellular gene expression. p38(XBL) is presumably translated from a doubly spliced, bicistronic mRNA that has the capability to encode another small polypeptide in a different reading frame.